Mechanism of Action of Surface Immobilized Antimicrobial Peptides Against Pseudomonas aeruginosa - Yasir, Muhammad; Dutta, Debarun; Hossain, Khondker R.; Chen, Renxun; Ho, Kitty K. K.; Kuppusamy, Rajesh; Clarke, Ronald J.; Kumar, Naresh; Willcox, Mark D. P. (Frontiers in Microbiology, 2020)
Bacterial colonization and biofilm development on medical devices can lead to infection. Antimicrobial peptide-coated surfaces may prevent such infections. Melimine and Mel4 are chimeric cationic peptides showing broad-spectrum antimicrobial activity once attached to biomaterials and are highly biocompatible in animal models and have been tested in Phase I and II/III human clinical trials. These peptides were covalently attached to glass using an azidobenzoic acid linker. Peptide attachment was confirmed using X-ray photoelectron spectroscopy and amino acid analysis. Mel4 when bound to glass was able to adopt a more ordered structure in the presence of bacterial membrane mimetic lipids. The ability of surface bound peptides to neutralize endotoxin was measured along with their interactions with the bacterial cytoplasmic membrane which were analyzed using DiSC(3)-5 and Sytox green, Syto-9 and PI dyes with fluorescence microscopy. Leakage of ATP and nucleic acids from cells were determined by analyzing the surrounding fluid. Attachment of the peptides resulted in increases in the percentage of nitrogen by 3.0% and 2.4%, and amino acid concentrations to 0.237 nmole and 0.298 nmole per coverslip on melimine and Mel4 coated surfaces respectively. The immobilized peptides bound lipopolysaccharide and disrupted the cytoplasmic membrane potential of P. aeruginosa within 15 min. Membrane depolarization was associated with a reduction in bacterial viability by 82% and 63% for melimine and Mel4 coatings respectively (p<0.001). Disruption of membrane potential was followed by leakage of ATP from melimine (1.5 ± 0.4 nM) or Mel4 (1.3 ± 0.2 nM) coated surfaces compared to uncoated glass after 2 h (p<0.001). Sytox green influx started after 3 h incubation with either peptide. Melimine coatings yielded 59% and Mel4 gave 36 % PI stained cells after 4 h. Release of the larger molecules (DNA/RNA) commenced after 4 h for melimine (1.8 ± 0.9 times more than control; p=0.008) and after 6 h with Mel4 (2.1 ± 0.2 times more than control; p<0.001). The mechanism of action of surface bound melimine and Mel4 was similar to that of the peptides in solution, however, their immobilization resulted in much slower (approximately 30 times) kinetics.